Beyond the transition phase of WTO :an Indian perspective on emerging issues / (Acc. 3904) an Indian perspective on emerging issues - Sengupta, Dipankar; Chakraborty, Debashis; Banerjee, Pritam; France. Ambassade (India). Centre for Human Sciences (New Delhi : Academic Foundation in association with Centre de Sciences Humaines, 2006)
Contributed articles on commercial policy and trade regulation in India in light of WTO policy.
Keywords: Trade regulation